Մուշեղ Իշխան. «Կյանքի և երազի սահմանագծին» - Հովհաննիսյան, Միհրան (Արմավ հրատ.)
Mushegh Ishkhan embodies the image of a man whose work is the direct embodiment of his lived life. A characteristic feature of his entire poetic system is that the collections were created and alternated in parallel with the stages of his life, according to the logic of the development of his inner world and worldview. He is a chronicle of his feelings, emotions, experiences, and his poetry collections are their personification and generalization. The collections are poetic manifestations of the experiences and anxieties of his generation, as well as instructions aimed not only at the Armenian wandering around the world, but also at the “strange human being” living under the sun: firstly, create your soul home in Armenian, build it in the vast space (“Song of Houses”, 1936), then kindle a flame covered with ashes, ignite the hearth (“Fire”, 1938), live your life like a dream, and dream like life (“Life and dream” 1949), accept the gifts of life (“Hello Life” 1958), and look back again and resign yourself to the fact that life is an experience, and a “strange human being” suffers (“Suffering” 1968), create, fertilize, and in the golden autumn distribute the harvest to everyone (“Golden Autumn”, 1963), and at the end of your life, realize that death is just a return to the primary, sympathize with the slow decomposition of your relatives (“Sunset”, 1986 .), before sunset, a little more, but brightly illuminate the world, praising the light and peaceful life, the meaning of life (“Evening St. under the bombs” 1991). Мушег Ишхан олицетворчет образ человека, творчество которого является непосредственным воплощением его прожитой жизни. Характерным признаком всей его поэтической системы является то, что сборники создавались и чередовались параллельно с этапами его жизни- по логике развития его внутреннего мира и мировоззрения. Он является летописью своих чувств, эмоций, переживаний, и его поэтические сборники являются их олицетворением и обобщением. Сборники- это поэтические проявления переживаний и тревог его поколения, а также наставления, направленные не только на армянина, скитающегося по всему миру, но и на «странное человеческое существо», живущего под солнцем: во-первых, создай свой дом души на армянском языке, построй его в необъятном космосе («Песня домов» 1936 г.), затем разжигай пламя, прикрытое пеплом, воспламени очаг («Огонь» 1938 г.), проживай свою жизнь, как мечту, а мечту- как жизнь («Жизнь и сон» 1949 г.), прими дары жизни («Здравствуй, жизнь» 1958 г.), и снова оглянись и смирись с тем, что жизнь- это переживания, и страдает «странное человеческое существо» («Страдания» 1968 г.), создавай, оплодотворяй, и золотой осенью всем раздавай плоды («Золотая осень» 1963 г.), а на закате своей жизни осознавай, что смерть- это всего лишь возвращение к первичному, сочувствуй медленному разложению своих сородичей («Закат», 1986 г.), до заката еще немного, но ярко освети мир, хваля свет и мирную жизнь, смысл жизни («Вечерний свет под бомбами» 1991 г.).
Keywords: Գրականություն